“We can’t survive without mutual support”: resilience and share and support networks in the Republic of Sakha (Russia) - Doloisio, Natalia; Vanderlinden, Jean-Paul (Frontiers in Climate, 2025)
This article analyzes the role of share and support networks (SSNs) in the Republic of Sakha (Russian Federation) in the context of accelerated climatic, environmental and socio-economic changes. The material associated to four fieldworks conducted in the Republic of Sakha has been mobilized: the first one in obtained Tiksi in November 2014, the second and third one in the city of Yakutsk in September 2015, and June 2018 respectively, and the fourth one in Tiksi and Bykovsky in July 2019. The qualitative analysis of the interviews revealed that food-centered SSNs are a salient topic in local narratives. They shape the current regional socio-economic configuration and play a key role in identity processes. They allow residents from different parts of the Republic of Sakha to have access to traditional food, but also enhance residents’ feeling of safety and wellbeing. Interviewees identified multiple manifestations of changes in climate and permafrost that are currently exerting increasing pressure on SSNs. These increase the difficulties to practice traditional activities and therefore to access black food (meat and fish) which is the base of the Yakutian diet. Local narratives demonstrate that the impacts of such changes on SSNs can exceed the merely local sphere and can entail severe and long-lasting consequences at a regional scale too. Furthermore, we identify shared representations of an ideal past—that of the Soviet Union—as an immaterial source of resilience through its potential to foster collective action.